The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1038/s41598-023-47269-4
|View full text |Cite
|
Sign up to set email alerts
|

Markers of insulin resistance associated with non-alcoholic fatty liver disease in non-diabetic population

Pei Zeng,
Xiangsheng Cai,
Xiaozhou Yu
et al.

Abstract: Insulin resistance (IR) plays an important role in the development of non-alcoholic fatty liver disease (NAFLD). IR markers are divided into two types: (1) insulin-based IR marker, homeostatic model assessment of IR (HOMA-IR); and (2) non-insulin-based IR markers, such as triglyceride-glucose (TyG) index, TyG index with body mass index (TyG-BMI), triglyceride/high-density lipoprotein cholesterol ratio (TG/HDL-c), and metabolic score for IR (METS-IR). The non-insulin-based IR markers are often associated with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The association between HOMA-IR and NAFLD has been already reported in previous studies, which found a higher diagnostic value compared to other insulin resistance (IR) markers [ 37 , 38 ]. Similar results were found for LAP; in a meta-analysis involving over 96,000 patients, the pooled sensitivity and specificity of LAP for screening NAFLD were 94% (95% CI 72–99%) and 85% (95% CI 62–96%), respectively [ 39 ].…”
Section: Discussionmentioning
confidence: 78%
“…The association between HOMA-IR and NAFLD has been already reported in previous studies, which found a higher diagnostic value compared to other insulin resistance (IR) markers [ 37 , 38 ]. Similar results were found for LAP; in a meta-analysis involving over 96,000 patients, the pooled sensitivity and specificity of LAP for screening NAFLD were 94% (95% CI 72–99%) and 85% (95% CI 62–96%), respectively [ 39 ].…”
Section: Discussionmentioning
confidence: 78%
“…Some of the aforementioned biochemical markers are widely acknowledged as risk factors closely associated with NAFLD, such as HOMA-IR and BMI. In our study, elevated HOMA-IR values were observed in the NASH group, indicating hepatic and adipose tissue IR attributing to NAFLD progression [ 30 , 31 ]. The role of platelets in the progression of NASH has been recognized.…”
Section: Discussionmentioning
confidence: 87%
“…Based on Model 2, the race, moderate activities, diabetes, SBP, education level, WC, drinking, TC, HbA1c, DBP, serum albumin, eGFR, TG were added as covariates to Model 3. Subgroup analyses stratified by BMI (<30 kg/m2 and ≥ 30 kg/m2), gender (male and female), diabetes (yes and no), age (<50 and ≥ 50 years), moderate activities (yes and no), education level (high school or above and less than high school) and drinking (yes and no) were conducted (19)(20)(21)(22). To examine the potential effect modification within subgroups, interaction terms were employed between subgroup indicators, followed by likelihood ratio tests.…”
Section: Discussionmentioning
confidence: 99%